2006
DOI: 10.1002/jcb.21087
|View full text |Cite
|
Sign up to set email alerts
|

Nucleo‐cytoplasmic cycling of the vitamin D receptor in the enterocyte‐like cell line, Caco‐2

Abstract: We examined the effects of 1,25 dihydroxyvitamin D 3 (1,25(OH) 2 D 3 ) on the distribution and mobility of the vitamin D receptor (VDR) in the enterocyte-like Caco-2 cell. Confocal microscopy showed that a green fluorescent protein-vitamin D receptor (GFP-VDR) fusion protein is predominantly nuclear (58%) and it does not associate with the apical or basolateral membrane of proliferating or polarized, differentiated cells. In contrast to the previously studied cell types, neither endogenous VDR nor GFP-VDR leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 40 publications
0
22
0
Order By: Relevance
“…We [26,27] and others [28,29], showed that nuclear accumulation of VDR is directly related to biological activity of 1,25D analogs. Given that VDR nuclear accumulation and pro-differentiating activity were correlated for previously tested analogs [27], we now studied how vitamin D 2 analogs influence expression of VDR in HL60 cells.…”
Section: Expression Of Vdr and C/ebpˇin Cells Exposed To 125d And Anmentioning
confidence: 95%
“…We [26,27] and others [28,29], showed that nuclear accumulation of VDR is directly related to biological activity of 1,25D analogs. Given that VDR nuclear accumulation and pro-differentiating activity were correlated for previously tested analogs [27], we now studied how vitamin D 2 analogs influence expression of VDR in HL60 cells.…”
Section: Expression Of Vdr and C/ebpˇin Cells Exposed To 125d And Anmentioning
confidence: 95%
“…RNA was isolated using TriReagent following the manufacturer's instructions (Molecular Research Center Inc., Cincinnati, OH). Total RNA (2 µg) was reverse transcribed to make cDNA and analyzed by real‐time PCR using primers and conditions previously described by our group [Wang et al, 2004; Klopot et al, 2006].…”
Section: Methodsmentioning
confidence: 99%
“…For all genes studied, mRNA expression was normalized to GAPDH mRNA expression, and data were expressed as arbitrary units. The primers used for CYP24 and GAPDH (Klopot et al, 2007), for VDR (Lou et al, 2005), and for Ets-1, ESE-1 and ESE-3 were previously described (Hollenhorst et al, 2004). Primers used for TRPV6 are: Forward primer: TTCCTGCGGGTGGAAGACAGGCA; Reverse primer: ACGCAGGTCTCTCCTCAGGGTC CC.…”
Section: Methodsmentioning
confidence: 99%